(untitled) (FAVE Sección Ciencias Veterinarias, 2024)
Shearing represents an acute stress for animals, the stress response of sheep during shearing has been described, but there is limited information on which factors trigger this response. With the Tally-Hi shearing method, the animals seem to be calmer than with traditional shearing with tied animals; the procedure has been improved and spread in recent years in Argentina. Our objective was to evaluate the effect of Tally-Hi shearing on the stress response in sheep; 20 2-year-old Merino breed females were randomly selected and two groups were formed. A: without shearing B: with shearing, all received the same peri-shearing management. Four whole blood samples were taken at different times: pre-shearing, immediately after shearing, 24 hours and 7 days post-shearing and glucose, total protein and cortisol levels were measured. No significant differences were found between the groups, but we observed a variation of both groups over time. We can conclude that the refinement of the shearing process (choice of the unmanaged Tally Hi method and operator training) was appropriate and does not generate additional stress to the peri-shearing management used in the Pilcaniyeu Experimental Field (herding, penning and vaccination).